A cross sectional study to determine the sociodemographic profile and study prevalence of chronic noncommunicable diseases in an urban slum of Mumbai - Chate, Priyanka D.; Nagpurkar, Ashirwad K.; Fernandes, Sophia; Shenoy, Anita G.; Patil, Vidula (International Journal Of Community Medicine And Public Health, 2021)
Background: Mumbai is the economic capital of India. According to 2011 census, 41.84% of total population of Mumbai city resides in slum areas; chronic noncommunicable diseases (NCDs) are the major cause of morbidity and mortality worldwide especially in developing countries where it has a huge impact on socioeconomic dynamics of the country and quality of life of its people. Methods: This was a retrospective cross sectional community level study based on family assessment survey records filled by undergraduate medical students as a part of their curriculum. The survey was conducted over the period of 1 years from August 2017 to July 2018 on 300 families residing in 3 slums in the field practice area of Cooper Hospital in Mumbai. Results: The total population was 1533, 720 were female and 813 were male. 417out of 1533 individuals were known cases of chronic noncommunicable diseases and were on treatment for the same, thus prevalence of chronic noncommunicable disease was 27.20%. There was significant association between age and prevalence of chronic noncommunicable disease (p<0.05) in the given population. Conclusions: The slum areas will continue to expand along with economic and industrial development. Growing number of slums constitute a major challenge to development of the community. The result emphasizes the need to implement measures to improve sanitation and hygiene of slums along with improvement of health coverage in these areas for early detection and treatment of NCDs.